The Influence of Social Media Marketing , Product Quality and Price Perceptions on Purchasing Decisions for Some Skincare Products - Sheila Isfara Saliha; Surono Surono (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
There are several common problems in the beauty industry related to these variables. In social media marketing, the level of competition is very high, with many brands vying for consumer attention. Small brands may struggle to stand out among the big brands. Products that don't suit a consumer's skin type or concerns can lead to negative experiences and damage a brand's reputation. Consumers' experiences influence their reviews and recommendations, which can have a positive or negative impact on the company (Susanti & Gunanto, 2022) .This research aims to identify the influence of social media marketing, product quality, and price perceptions on purchasing decisions for Somethingnc skincare. The sample was determined using a purposive sampling technique with a total of 100 respondents. The validity and reliability of the questionnaire were tested using the SPSS 23 tool. The results of this research show that social media marketing, product quality, and price perceptions have a significant positive influence on purchasing decisions.